THE ECONOMIC DEVELOPMENT OF UZBEKISTAN’S SERVICES SECTOR - E. Nabiev (Web of Journals Publishing, 2025)
In this scientific article, an evaluation model of the service industry was created, and in this scientific model, the development of the service industry turns into digital services, which shows that it is related to the daily life of mankind. Therefore, in this scientific article, the terms service delivery and digital services are defined scientifically.
Keywords: Service, digital services, digital economy, innovation, industrial, postindustrial, agrarian society, communication and information, communication, evolution, model.